Designing Pop-Up Book Media in Developing English Reading - Nela Yuningsih; Tatu Siti Rohbiah; Apud Apud (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
The objectives of the study are: 1) to identify how to develop Pop-Up book learning media on descriptive text material; 2) to determine the feasibility of Pop-Up book learning media on descriptive text material; and 3) to identify the students’ responses to the learning media on the descriptive text material. This study used Research and Development methods (Research and Development) using the ADDIE model. The subjects in this study were students at MTs Al-Khairiyah Pontang. The data were obtained from observations, interviews, and questionnaires. The results of this study focus on the use of the Pop-Up book learning media on descriptive text material. The quality of the Pop-Up book learning media based on the results of the media expert’s assessment is in an average score of 4.50, from material experts, it obtains an average score of 4.83, and from educators’ experts, the average score is 4.65. All the results of the questionnaire recapitulation at the product validation stage have very feasible criteria, as well as students’ responses in the very attractive category, and students’ responses in the field trials obtain an average percentage of 90.8% with a very attractive category. Based on the assessments of media experts, material experts, educator experts, and students’ responses, it can be concluded that the Pop-Up book on descriptive text material is feasible to be used as a learning medium